Effect of sowing dates of irrigated rice on the intensity of diseases in south Paraguay (Journal on studies and research of academic knowledge, 2024)
The fungal diseases such as neck blast, brown spot and grain discoloration affect the productive potential and quality of rice. Management practices such as sowing date can have a positive or negative influence on disease intensity. In this context, the objective was to evaluate the effect of the different sowing dates of irrigated rice on the intensity of these diseases, through the quantification of the intensity of damage and the identification of pathogens associated with grain discoloration. The experiment was carried out in the 2020/2021 growing season, at the experimental station of Arrozal S.A company, Itapúa, Coronel Bogado and at the Phytopathology Laboratory, Faculty of Agrarian Sciences-UNA. Each experimental unit (UE) consisted of 5 m2, made up of 8 rows of plants spaced 20 cm apart, with a density of 80 kg ha-1 of seeds of the cultivar Irga 424. The design was DBCA with 4 replications, in a subdivided plot scheme. The plots consisted of the sowing times and the subplots in areas without protection and with protection The sowing dates were: 09/01, 09/29, 10/23, 11/25. The intensity of damage of neck blast and Brown spot increased in late sowing (25/11), negatively affecting grain yield, however the incidence of grain discoloration was not influenced by the sowing time. The fungi associated with the grain discoloration were Bipolaris, Curvularia, Nigrospora, Alternaria, Fusarium and Epicocum.
Keywords: Bipolaris oryzae; Pyricularia oryzae; Oryza sativa L; sowing date; Intensity of damage